A DFT study of the interaction of Ox with Pt nanorod edge sites : a model for the ORR activity on Pt nanoparticle edges - Gambu, Gorden Thobani (Department of Chemical Engineering, 2016)
Proton exchange membrane fuel cells (PEMFCs) are an attractive energy conversion technology, this due to their high theoretical fuel utilization efficiencies compared to Carnot engines. However, due to potential losses, the operational efficiencies achieved in state-of-the-art PEMFCs are only between 45% and 55%. The slow kinetics of the oxygen reduction reaction (ORR) over a platinum based electrode accounts for ca. 70% of the potential losses. As a result of the sluggish ORR kinetics, high platinum loadings are required. The high cost of platinum has made it crucial to improve the ORR activity and hence reduce platinum loading. The surface-area-specific ORR activity has been reported to decrease with platinum particle size. This places a limitation to the degree to which platinum loading can be reduced by increasing metal dispersion. To understand the origin of this behaviour, experimental studies have measured the ORR activity over different single crystalline surfaces and used model nanoparticle shapes to elucidate the overall ORR activity. Theoretical studies use density functional theory (DFT) to investigate the ORR activity on various site-types present on assumed model particle shapes. Thermodynamically, the exposed surface terminations aught to be predominantly Ptf111g and Ptf100g separated by edges and corners. It has been postulated that the overall ORR activity can be calculated as a weighted average of the activity of exposed surface terminations. Using DFT calculations and nanorod models the above postulations are tested for the edge sites between a Pt(111) and Pt(100) surface. A rhombic nanorod model is used due to its computational efficiency compared to model nanoparticle clusters which are generally large and computationally expensive models. Furthermore, the use of rhombic nanorod model enables the investigation of the connection and communication between the Pt(111) and Pt(100) facets, this is difficult to investigate with stepped-surface models. It is argued that if, (i) the edge has insubstantial effect on the adsorption strength of adsorbed ORR intermediates as a function of distance from the edge and (ii) the diffusion of ORR intermediates between adjacent surface planes is limited, then the above postulation does hold.